2023
DOI: 10.1093/plphys/kiad359
|View full text |Cite
|
Sign up to set email alerts
|

SPOTTED-LEAF7 targets the gene encoding β-galactosidase9, which functions in rice growth and stress responses

Abstract: β-Galactosidases (Bgals) remove terminal β-D-galactosyl residues from the non-reducing ends of β-D-galactosides and oligosaccharides. Bgals are present in bacteria, fungi, animals, and plants and have various functions. Despite many studies on the evolution of BGALs in plants, their functions remain obscure. Here, we identified rice (Oryza sativa) β-galactosidase9 (OsBGAL9) as a direct target of the heat stress-induced transcription factor SPOTTED-LEAF7 (OsSPL7), as demonstrated by protoplast transactivation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In rice, the functional analysis of knockout plants for OsBGAL9 underscored the pivotal role of BGALs. The observed phenotype, marked by short stature and growth retardation, highlights the significance of OsBGAL9 in the regulation of rice plant growth and development [30]. The conservation of all MrBGALs was generally high, with the exception of MrChr3G28800, which contained the Glyco_hydro_35 domain motif.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In rice, the functional analysis of knockout plants for OsBGAL9 underscored the pivotal role of BGALs. The observed phenotype, marked by short stature and growth retardation, highlights the significance of OsBGAL9 in the regulation of rice plant growth and development [30]. The conservation of all MrBGALs was generally high, with the exception of MrChr3G28800, which contained the Glyco_hydro_35 domain motif.…”
Section: Discussionmentioning
confidence: 87%
“…The protein subcellular location of the BGAL in melon and Arabidopsis showed that they were mainly located in extracellular space (cell wall) [11]. The BGAL play significant roles throughout a plant's lifecycle, influencing plant growth and development, including fruit softening [22][23][24][25][26], fruit development and ripening [19,27,28], seed germination [29], stress responses [30,31], and root development [32]. Furthermore, β-galactosidase is believed to expedite fruit softening [33].…”
Section: Introductionmentioning
confidence: 99%
“…LOC_Os12G24170 is a precursor of beta-galactosidase enzyme (BGAL) that mediates the physiological process of seed germination through cross talks among GA and Abscisic acid (ABA) to determine grain yield in rice [ 3 ]. Knockout studies revealed that BGAL9 regulates different physiological functions and stress responses in rice [ 108 ]. Transcriptomics studies very well implied the upregulation of OsBAGL1, OsBAGL4, OsBAGL8 and OsBAGL11 genes during seed germination and their influence on plant growth and development [ 109 ].…”
Section: Discussionmentioning
confidence: 99%